The legend of Zelda. Twilight princess. Volume 9 - Himekawa, Akira; Stan!, 1964- (The legend of Zelda, 2021)
"Midna tells Link about the time before she came to the world of Light and how she was changed into her current form. Bitter and angry, Midna only used other people to get her revenge. Link needs Midna's help now more than ever and his forgiveness may give her the strength to continue the fight. Ahead of them, in the Twilight Realm itself lie greater dangers then they have faced before, as well as Midna's nemesis the scheming Zant."--Back cover.